Studi Pelayanan Administrasi Terhadap Kepuasan Mahasiswa Di Jurusan Teknologi Pertanian (TP) Universitas Bengkulu - Lestari, Ela Sri; Anis, Ulfah; Fatharani, Arina; Setiawan, Trio P; Darmatama, Iman (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Organizations are assessed based on academic services, especially to students. A college operates based on student satisfaction. The best services must be offered by the academic sector. Providing exceptional customer service is crucial for business success, particularly for companies and establishments in the service industry. The purpose of this study is to determine how satisfied students are with the administrative services provided by Bengkulu University's Department of Agricultural Technology. In this study, all enrolled students majoring in Agricultural Technology at the Faculty of Agriculture, Bengkulu University. Descriptive and quantitative research methods used simple random sampling were used for this research. through their perceptions of the quality of academic services. Using a straightforward random sampling method, SPSS software was used to handle the research sample. By examining the quality from the tangible aspect of the physical evidence, the aspect of reliability, the element of responsiveness, the aspect of assurance, and the aspect of empathy, students can gauge how satisfied they are with academic services. According to the study's findings, the evaluation of satisfaction comprises the following elements: physical aspects (tangible) at 86%, aspects of reliability (84%), aspects of responsiveness (86%), aspects of assurance (68%), and aspects of empathy (92%).